Isopropanol Dehydration on Amorphous Silica–Alumina: Synergy of Brønsted and Lewis Acidities at Pseudo‐Bridging Silanols. (2nd December 2016) - Larmier, Kim; Chizallet, Céline; Maury, Sylvie; Cadran, Nicolas; Abboud, Johnny; Lamic‐Humblot, Anne‐Félicie; Marceau, Eric; Lauron‐Pernot, Hélène
Abstract: The mechanism of isopropanol dehydration on amorphous silica–alumina (ASA) was unraveled by a combination of experimental kinetic measurements and periodic density functional theory (DFT) calculations. We show that pseudo‐bridging silanols (PBS‐Al) are the most likely active sites owing to the synergy between the Brønsted and Lewis acidic properties of these sites, which facilitates the activation of alcohol hydroxy groups as leaving groups. Isopropanol dehydration was used to specifically investigate these PBS‐Al sites, whose density was estimated to be about 10 −1  site nm −2 on the silica‐doped alumina surface under investigation, by combining information from experiments and theoretical calculations. Abstract : Zusammenspiel zweier Arten von Säure : Periodische Ab‐initio‐Rechnungen und kinetische Messungen wurden kombiniert, um die katalytisch aktiven Zentren bei der Dehydratisierung von Isopropylalkohol über amorphem SiO2 /Al2 O3 zu bestimmen. Pseudo‐verbrückende Silanole, die Lewis‐ und Brønsted‐Säuren sind, spielen in dieser Reaktion eine entscheidende Rolle.